Development of Electronic Student Worksheets Based on TPS Model Assisted by Nearpod on Reaction Rate Material - Suhana, Mely Dwi; Rasmiwetti, Rasmiwetti; Erviyenni, Erviyenni (Pendidikan Kimia FKIP Universitas Jambi, 2025)
The rapid development of science and technology requires the education system to adapt in order to improve the quality of education. One effort to enhance educational quality is by utilizing appropriate teaching materials, such as Electronic Student Worksheets. The Electronic Student Worksheets developed in this study employed the Think Pair and Share (TPS) learning model. This research is a Research and Development (R&D) study using the ADDIE model, motivated by the absence of Electronic Student Worksheets in chemistry learning at schools. The objectives of this study were to develop TPS-based Electronic Student Worksheets assisted by Nearpod on the topic of reaction rates, and to evaluate user responses toward the worksheets. The material validation results in the aspects of content, TPS model characteristics, language, presentation, and visual design were 94.65%, 95.84%, 100%, 91.67%, and 96.88%, respectively, categorized as valid. The media validation results for worksheet size, cover design, and content layout were 100%, 100%, and 92.71%, also categorized as valid. User responses from teachers, covering aspects of content and language clarity, TPS model characteristics, attractiveness, and practicality, were 97.8%, 95.8%, 95.8%, and 87.5%, respectively, categorized as very good. Student responses, which assessed the aspects of attractiveness, content and language clarity, and practicality, were 90.3%, 87.3%, and 81.3%, respectively, also falling under the very good category. Keyword: Electronic Student Worksheets, Nearpod, Think Pair and Share, Reaction